In situ oxygen-isotope, major-, and trace-element constraints on the metasomatic modification and crustal origin of a diamondiferous eclogite from Roberts Victor, Kaapvaal Craton. (1st February 2016) - Riches, A.J.V.; Ickert, R.B.; Pearson, D.G.; Stern, R.A.; Jackson, S.E.; Ishikawa, A.; Kjarsgaard, B.A.; Gurney, J.J.
Abstract: A subducted oceanic crustal origin for most eclogite xenoliths in kimberlites has long been a cornerstone of tectonic models for craton development. However, eclogite xenoliths often have protracted and complex histories involving multiple metasomatic events that could overprint some of the key geochemical indicators typically taken as evidence of a subducted origin (e.g., garnet δ 18 O-values and mineral 87 Sr/ 86 Sr compositions). To assess the potential for disturbance of oxygen isotopic compositions in mantle eclogites via diamond-forming and other possible metasomatic fluids, we have conducted a multi-technique in situ study of a diamondiferous eclogite xenolith from the Roberts Victor kimberlite, S. Africa. Using SIMS we provide the first texturally-controlled in situ measurements of δ 18 O-values in eclogitic garnet in close proximity to diamond. Garnet and clinopyroxene modal proportions are heterogeneous in the xenolith and garnet compositions vary from Mg# = 75.8–79.2; grossular proportions = 8.05–10.14 mol.%, and omphacitic pyroxene has Jd13–24 and Mg# = 86.6–90.0. Rare earth element patterns of minerals across the xenolith, including grains close to diamond, are typical LREE-depleted garnets and markedly LREE-enriched pyroxenes. These silicate minerals also record detectable intra- and inter-grain LREE abundance variations. Clinopyroxenes of the studied xenoliths show HFSE and Sr abundance variations that are decoupled from LREE contents and major-element variations. Mineralogical constraints and bulk-rock reconstructions indicate that the studied sample likely experienced selective incompatible element enrichment during small-volume (<<0.03 wt.%) infiltration of metasomatic fluid(s) potentially linked to ancient diamond evolution. Intra-grain major-element, LREE and HFSE variations in clinopyroxene resulted from late-stage metasomatism. Oxygen isotope compositions in garnet are decoupled from all major- and trace-element variations, with garnet δ 18 O-values being uniform across the xenolith in a wide variety of textural settings. Garnet δ 18 O-values of +6.5 ± 0.2 ‰ are higher than the mean (+5.19 ± 0.26 ‰) of the mantle garnet range (+4.8–5.5 ‰). Modelling of the buffering effect of mantle peridotite on CO2 -rich and H2 O-rich metasomatic fluids at temperatures within the diamond stability field indicates that the likelihood of a metasomatic fluid with exotic oxygen isotopic composition arriving at a mantle eclogite body with its isotopic composition unmodified, after percolative flow through dominantly peridotitic mantle at great depth, is very low. As we find no evidence of metasomatically induced garnet oxygen isotope variations in the studied diamondiferous eclogite xenolith we conclude that the most likely origin for the elevated garnet δ 18 O-values is via inheritance from a crustal protolith altered at relatively low temperatures. These results have broader relevance and support the hypothesis of a low-pressure protolith for mantle eclogite xenoliths, demonstrating the robust nature of garnet oxygen isotope compositions – even in diamond-bearing eclogites.